Revision of Odontophotopsis Viereck (Hymenoptera: Mutillidae), Part 1, with a description of a new Genus Laminatilla - Pitts, James P. (Zootaxa, 2007)
This study presents part 1 of a revision of Odontophotopsis Viereck (Hymenoptera: Mutillidae) and includes the cockerelli, dentifera, exogyra, hexadonta, quadridentata, setifera, tenuiptera, and unicornis species-groups sensu Schuster (1958), representing 14 species. This revision also includes the sonora species-group, which contains Odontophotopsis sonora (Schuster), new comb., and the villosa species-group, which is newly defined and contains O. villosa Mickel. Odontophotopsis polis, sp. nov., is described from Baja California and is placed in the O. dentifera species-group. Odontophotopsis mexicana, sp. nov., and O. costaricensis, sp. nov., are described from Mexico and Costa Rica, respectively, and are placed in the O. tenuiptera species-group. A neotype is designated for O. unicornis Schuster. Keys are provided to the Odontophotopsis species-groups and to the species in these species-groups, where appropriate. Odontophotopsis (Periphotopsis) mamata Schuster is placed in the O. parva species-group and Periphotopsis is a junior synonym ofOdontophotopsis. Odontophotopsis rubriventris (Schuster), new comb., was previously placed in Sphaeropthalma Blake. Photomorphus piceogaster (Schuster), new comb., was previously placed in Odontophotopsis. A new genus Laminatilla, gen. nov. (type species Odontophotopsis lamellifera Schuster 1958), is described. This new genus includes the three species L. bicornigera (Schuster), comb. nov., L. lamellifera (Schuster), comb. nov., and O. mixtoensis Schuster (Schuster), comb. nov., which were previously placed in the O. lamellifera species-groups sensu Schuster (1958). A key to the species of Laminatilla and a new key for the males of the Nearctic genera of nocturnal mutillids are provided.